2021
DOI: 10.7717/peerj.11905
|View full text |Cite
|
Sign up to set email alerts
|

DOG1 is commonly expressed in pancreatic adenocarcinoma but unrelated to cancer aggressiveness

Abstract: Background DOG1 (ANO1; TMEM16A) is a voltage-gated calcium-activated chloride and bicarbonate channel. DOG1 is physiologically expressed in Cajal cells, where it plays an important role in regulating intestinal motility and its expression is a diagnostic hallmark of gastrointestinal stromal tumors (GIST). Data on a possible role of DOG1 in pancreatic cancer are rare and controversial. The aim of our study was to clarify the prevalence of DOG1 expression in pancreatic cancer and to study its asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…34,35 ANO1, which encodes a 960-amino acid protein with 8 transmembrane domains, is highly deregulated in different tumors. 7,8,13,36 As an oncogenic factor, Ano1 can promote cell movement, adhesion, and invasion. Previous studies have found that ANO1 can inhibit the growth and invasion of ovarian cancer by blocking the PI3K/Akt signaling pathway, which is useful in prognosis analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34,35 ANO1, which encodes a 960-amino acid protein with 8 transmembrane domains, is highly deregulated in different tumors. 7,8,13,36 As an oncogenic factor, Ano1 can promote cell movement, adhesion, and invasion. Previous studies have found that ANO1 can inhibit the growth and invasion of ovarian cancer by blocking the PI3K/Akt signaling pathway, which is useful in prognosis analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the description provided in the methods section, we constructed the PPI network of the top three modules (gold, steel blue, and turquoise) in terms of the number of genes (Figure 9A-C). PPI-gold contains 94 nodes (42 upregulated The Hub nodes with higher level rankings were PPI-gold: KNG1 (21), GNG4 (19), F2 (15); PPI-steel blue: POSTN (8), THBS2 ( 7), SPP1 (6); and PPI-turquoise: FGA (7). These genes frequently interact with other proteins in each module and are important nodes in the network.…”
Section: Ppi Network Construction and Key Node Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this retrospective study, the TMA was constructed as previously described by Kononen et al 16 The TMA included 532 primary pancreatic cancers, 61 primary adenocarcinomas of the ampulla Vateri, and 6 primary pancreatic acinar cell carcinomas from the Institute of Pathology of the University Medical Center Hamburg-Eppendorf (Table 1). 17 The tumor samples were consecutively collected from patients who underwent different types of pancreatectomy at the Department of General- Visceral- and Thoracic-Surgery, University Medical Center Hamburg-Eppendorf between 1993 and 2005, and were selected for sufficient amounts of cancer cells in the paraffin block. A single 0.6 mm core per tumor was sampled for TMA construction.…”
Section: Methodsmentioning
confidence: 99%
“…This approach allows direct delivery of highly potent cytotoxic agents to antigen-positive tumor tissue with limited off-target toxicities (19). Since the first ADC, Mylotarg ® (gemtuzumab ozogamicin), was approved in 2000 by the US Food and Drug Administration (FDA) against CD33-positive acute myeloid leukemia (AML), there have been 14 ADCs received market approval (20,21), and over 100 ADCs are currently under clinical development. However, half of these 14 ADCs approved by FDA are mainly used against hematological malignancies such as AML and anaplastic large cell lymphoma (ALCL).…”
Section: Introductionmentioning
confidence: 99%